Frequency of Asymptomatic Spontaneous Bacterial Peritonitis in Patients with Decompensated Chronic Liver Disease (Medical Forum Monthly, 2024)
Objective: To determine the frequency of asymptomatic spontaneous bacterial peritonitis (SBP) in patients with decompensated chronic liver disease (DCLD).Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Gastroenterology, PGMI/Hayatabad Medical Complex, Peshawar, from 06-09-2022 to 06-03-2023.Methods: A total of 164 patients aged 16-75 years, both genders, with DCLD-associated ascites were enrolled. Ascitic fluid samples were collected to identify the presence of SBP through polymorphonuclear (PMN) counts without clinical symptoms of SBP.Results: The mean age was 56.25 ± 16.68 years, with 53% male and 47% female patients. Among the enrolled patients, 3.7% (n=6) had asymptomatic spontaneous bacterial peritonitis. The most frequent cause of DCLD was hepatitis C (39.6%), followed by hepatitis B (22.6%).Conclusion: The study found that 3.7% of patients with DCLD had asymptomatic SBP. Screening for SBP in asymptomatic patients is recommended to reduce potential morbidity and mortality associated with this hidden condition.